Analysis of the Implementation of the Occupational Safety and Health (OSH) Program in the Operation Unit at Lempuyangan Station PT KAI (Persero) Operating Area (DAOP) VI Yogyakarta - Oktavia Eka Saputri; Hariyono, Widodo (Universitas Ahmad Dahlan, 2024)
Background: PT Kereta Api Indonesia (Persero) has a commitment to always consistently and without compromise in implementing a railway safety management system in order to realize the company's vision of becoming the best transportation ecosystem solution for Indonesia through railway operational services and a safe, healthy, secure and comfortable working environment and sustainable environmental preservation. The aim of this research is to determine the implementation of the K3 program in the Lempuyangan station operating unit. Method: The method used in this research is descriptive qualitative. Results: The research results show that all K3 implementations such as K3 SOPs, K3 signs and PPE are available and have been implemented, as for the K3 implementations in operating units, namely (1) briefing before work; (2) use of Personal Protective Equipment (PPE) when working; (3) providing safe boundaries on platforms, for example yellow lines along the platform path; (4) comply with work procedures and report if there is a potential danger nearby. Even though there is an K3 implementation program in the Lempuyangan station operating unit, there is no special team such as HSE that monitors workers' compliance with K3 implementation directly every day, only from superiors such as the station head and deputy station head. The special team that supervises and controls is from the center which will come but only periodically. But even so, the K3 SOP still works and is implemented well. Conclusion: the implementation of the K3 program in the Lempuyangan station operating unit has been carried out well but must be monitored so that it continues to run well.